VIRTUAL REALITY AND ITS IMPORTANCE IN MODERN LIFE - Shavkiev Oybek; Shavkieva Maftuna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on virtual reality, reality, virtual reality, the concept of virtual reality and its application in various fields. Also, opinions about the importance of virtual reality in today’s modern world, its specific features and virtual reality technologies are also presented.